THE IMPACT THAT SOCIAL MEDIA HAS HAD ON TODAY'S GENERATION OF INDIAN YOUTH: AN ANALYTICAL STUDY - Showkat Dar; Dolly Nagrath (RADJA PUBLIKA, 2022)
Social media has become a daily habit in most people’s lives. People of all ages participate in social media, and the average Indian devotes nearly 2.4 hours per day to this one activity alone. People are able to voice their concerns and share their perspectives through the medium of social media. When it comes to understanding social media, people must first be comfortable with the notion. Users can communicate with one another and share information, thoughts, opinions, images, and videos via Internet-based programmes known as